More than the shadow of a doubt: dream theory and the impersonation of saints by angels - Dirk Krausmuller (Mukaddime, 2018)
This brief article makes the case that the 'uncritical' acceptance of the real presence of saints in dreams by the participants of the Second Council of Nicaea did not reflect the usual attitudes of the Byzantine elite. It shows that earlier and later writers denied such presence through recourse to dream theory, which attributed all 'good' dreams to the agency of angels.